Atividades anti-inflamatória e antirreabsortiva ósseas do ácido zoledrônico durante a movimentação dentária induzida em ratos - Kurita, Bianca Moreira (2017)
The induced tooth movement (ITM) combines bone resorption and neoformation that depends on chemical mediators of inflammation, thus culminating in bone remodeling. This observation has encouraged the evaluation of the effect of zoledronic acid (ZOL), a bisphosphonate that inhibits osteoclastic activity, being widely used for treating bone metabolic disorders, such as osteoporosis and bone metastasis. However, literature has not addresses the participations of proinflammatory cytokines on RANKL-OPG axis modulation during MDI and ZOL treatment. On this, we evaluated the effect of ZOL on bone remodeling of ITM. ITM was performed in 72 anesthetized Wistar rats by the installation and activation of a nickel-titanium coil-spring, with 50 gf, fixed on upper left 1st molar and upper incisors. The same received distilled water, being considered as non-treated group (NT - 1 ml/kg-i.v.) or ZOL (50, 100 e 200 g/kg-iv), 5 minutes before the dispositive insertion, and on 7th day. On day zero, blood samples were collected for leukogram assay (mm3) and bone alkaline phosphatase dosage (BALP: U/I), and the space between the teeth were measured. On the 11th day, the collects and measures were repeated and the gingivas and hemimaxillas were removed for myeloperoxidase activity dosage (MPO: 103 mg of tissue) and TNF- e IL-1 gingival levels analysis (pg/mg of tissue), histomorphometric analysis of periodontal ligament areas of compression, traction and hyalines, histological evaluation by scores (0 to 3) of root and bone resorptions and immunohistochemical staining for RANKL, OPG, TRAP, TNF- e IL-1. The animals were weighted daily during the all-experimental period, and then, were related to basal values; Ethics Committee on the Use of Animals-UFC nº 28/15. The NT group, had an increase of tooth movement, high scores of root and bone resorption, increased activity of MPO and high gingival levels of TNF- e IL-1, intense immunostaining for RANKL, TRAP e TNF- on the compression side and for RANKL and OPG on the traction side of periodontal ligament, resulting on increased RANKL/OPG ratio on compression side (p<0.05). Still, they do not presented changes in serum levels of BALP, in total and differential leukogram assay and histomorphometric analysis (p>0.05), but they lost weight initially, being the initial weight, recovered from the 7th day. ZOL treatment in three doses used reduced tooth movement in a dose-dependent manner, as well as resulted in low scores of root and bone resorption and reduction of MPO activity. However, ZOL in the high dose (200 g/kg) did not change TNF- e IL-1 gingival levels (p>0.05). Still, this dose reduced the immunostaining of TRAP on compression side, OPG on traction side and RANKL and TNF- on both sides, resulting on a decrease of RANKL/OPG ratio on both regions analyzed (p<0.05). In addition, ZOL treatment did not induce changes on leukogram values and body mass variation in comparison to the animals that received dH2O (p>0.05). In short, ZOL reduced the ITM by decreasing bone biomarkers essential for osteoclastic differentiation and activity and reducing bone anabolism.